Forecasting tropical cyclone movement by statistical and dynamical techniques - Wattana Kanbua (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
Based on the fact that tropical cyclone movement is highly correlated with the parameters related to the climatology and persistency of tropical cyclone movement, a statistical model for forecasting tropical cyclone movement has been developed. This method employs the stepwise screening procedure and Dynamical Techniques. Thai Meteorological Department uses this method in the routine on-line system, when it is necessary. This method was computed from the tropical cyclone data,1945-1989 and tested using the tropical cyclone forecast verification data from 1983-1987. This model in conjunction with use of satellite and GTS studies has been very successful for predicting cyclone movement in the Thailand area of responsibility.